Seasonal variation of Guillain-Barré syndrome in Iranian patients: a retrospective study - Hossein Hatami; Farzad Fatehi; Ramin Heshmat; Elham Dirandeh (Shahid Beheshti University of Medical Sciences, 2021)
Background: It seems that the incidence of Guillain-Barré syndrome (GBS) has seasonal trends depending on weather as well as environmental and demographic factors such as upper respiratory tract infection (URI). The aim of this study was to evaluate seasonality of GBS and its electrophysiological subtypes. Methods: In this cross-sectional study, the records of all admitted patients to all wards of Dr. Shariati Hospital from March 2009 to March 2019 according to ICD-10 codes for GBS and other similar neuropathies were investigated and 87 patients were registered based on fulfillment of Brighton criteria and symptom onset during the recent 4 weeks. Statistical analysis was performed by IBM SPSS version 20. A p-value < 0.05 was considered statistically significant. Results: Most of the patients (63.2%, n=55) were men. The mean age of them was 49.1±19.2 years, and 41.3% (n=36) and 10.3% (n=9) participants had recent URI and gastrointestinal infection, respectively. The frequency of GBS in different seasons was 35.6% (n=31) patients in the winter, 27.6% (n=24) in the autumn, 19.6% (n=17) in the spring, and 17.2% (n=15) in the summer. The most frequent electrophysiological subtype was acute inflammatory demyelinating polyneuropathy (AIDP) in all seasons. The most common GBS disability score was 1. Conclusion: The highest and the lowest occurrence was seen in the winter and summer, respectively. AIDP was the most common electrophysiological subtype in all seasons. More studies are suggested to evaluate other aspects of GBS on more details.